Software organizational forms management of economic activities bodies russian extraordinary commission and state political control during formation of new economic policy - Комиляй, Юрій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article deals with procedural and institutional forms of economical activity management. There aregiven the features of modern understanding of such forms as well as author‘s definition of procedural and institutional forms of economical activity management within context of research subject. There was also analyzed the provision of procedural and institutional forms of economical activity management by properbodies of All-Russian Extraordinary Commission and State Political Directorate during new economic policy implementation, undertaken by Soviet government.